1999
DOI: 10.1097/00001756-199907130-00021
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line derived neurotrophic factor (GDNF) regulates VR1 and substance P in cultured sensory neurons

Abstract: Many nociceptive dorsal root ganglion (DRG) sensory neurons express the high affinity nerve growth factor (NGF) receptor TRKA, and respond to NGF. However, many do not express TRKA but are thought to respond to glial cell-derived neurotrophic factor (GDNF) and related molecules. We therefore cultured DRG neurons in the presence of GDNF, and looked at the expression of substance P and of the capsaicin receptor, VR1, two nociceptive properties already known to be NGF regulated. Using several different approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 5 publications
2
47
2
Order By: Relevance
“…It is reported that GDNF may contribute to the regulation of nociceptive properties in cultured sensory neurons [Ogun-Muyiwa et al, 1999]. Thus, GDNF and BDNF may be involved in the nociceptive neurotransmission at lamina I to II of the spinal dorsal horn to which DRG neurons project centripetal axon terminals.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that GDNF may contribute to the regulation of nociceptive properties in cultured sensory neurons [Ogun-Muyiwa et al, 1999]. Thus, GDNF and BDNF may be involved in the nociceptive neurotransmission at lamina I to II of the spinal dorsal horn to which DRG neurons project centripetal axon terminals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to posttranslational regulation, NGF might regulate TRPV1 mRNA levels. Over extended culture periods (3-10 days) of DRG neurons from adult rats, NGF can maintain higher numbers of TRPV1-mRNApositive and TRPV1-immunoreactive cells (Ogun-Muyiwa et al 1999;Bron et al 2003) and increase TRPV1 mRNA levels in comparison with controls as found by Northern Blot (Winston et al 2001). NGF also prevents the decline in the number of cold-sensitive DRG neurons with time in culture as analysed via the cold-induced elevation of intracellular calcium concentration (Babes et al 2004).…”
Section: Ngf Is Involved In Embryonic Regulation Of Trp Channel Exprementioning
confidence: 96%
“…Second, the density of sympathetic sprouts in the DRG does not correlate with neuropathic pain intensity (8). Given that 1) DRG neurons express receptors for satellite cell-derived proinflammatory cytokines and growth factors (204,216) and 2) these proinflammatory cytokines and growth factors act in a paracrine fashion to influence large numbers of cells, perhaps it may be that these satellite cell-derived substances are really the basis for altered pain, rather than the sympathetic sprouts. From this perspective, sympathetic sprouting into DRGs may simply be a "side effect" of glial activation.…”
Section: C) Implications Of Sympathetic Nervous System Involvementmentioning
confidence: 99%